PROTEIN ADHESIN 38-KDA MIKOBAKTERIUM TUBERKULOSIS DAN SEL MAKROFAG PARU - Maimun Zulhaidah A; Rahmawati Rahmawati; Bethasiwi Purbasari; Sumarno Sumarno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Tuberculosis (TB) in Indonesia is at the third level in the world. The effectiveness of TB vaccine in lung TB. prevention varies, thus,this has motivated the researcher to explore based material of vaccine with a higher effectivity. One of the alternate vaccines that hasdeveloped, is the sub unit one made from adhesin protein. The aim of this study was to know the kind of oral administration of 38 kDaadhesin protein of M. tuberculosis in determining so that it can increase the level of macrophage in lungs of BALB/c mice. This study wasan experimental work using BALB/c male mice that were immunized with 38 kDa adhesin protein of Mycobacterium tuberculosis orally.The samples were chosen at random and divided into six (6) groups that consisted of: “100 μg protein +adjuvant ImmunostimulatingComplex (ISCOM)” group (n=5), “50 μg + adjuvant ISCOM” group (n=5), “100 μg” group (n=5), “50 μg” group (n=5), “ISCOM” group(n=5) and “negative control” group (n=5). The measurement of the variable in this study was the number of macrophages . The resultsshowed that the increasing number of macrophage had significant differences between each group. ANOVA test showed a significant levelat p<0.05. The conclusion of this study was that 38 kDa adhesin protein of M. tuberculosis peroral could increase the level of macrophagein the lung of BALB/c mice. The highest level of macrophages was the group induced by 100 μg 38 kDa adhesin protein of M. tuberculosisand adjuvant ISCOM.